(untitled) (Economics and region, 2023)
In the conditions of global risks, the main prerequisite for the stabilization of the economy is strategic planning, which actively began to develop in European practice since 2015 after the UN General Assembly meeting, where the main issue was the implementation of a single globalized economy in the aspect of sustainable development. As a result of the meeting, 17 goals of sustainable development and 169 tasks were determined. The development of regions separately, as an object of social national development, has become the main vector of strategic planning of European countries. Accordingly, in the process of active European integration, since 2015, Ukraine has developed its own sustainable development strategy, "Sustainable Development Strategy of Ukraine - 2020", which was based on reforms of decentralization, education, health care, etc. There were few changes to the Tax and Budget Code of Ukraine. However, the first stage of the implementation of the reforms was unsuccessful and only 4 goals out of 17 could be achieved. Despite this, there are significant shifts in the development of regions. In 2020, the first stage of reforms ended and it is important to monitor in all aspects and sectors. An important part of the reform is financial decentralization as the basis of the economic foundation of regional development. The article analyzes the impact of the decentralization reform on the financial and economic indicators of the region and the country in general from the moment the reform began until the end of the first stage of its existence. Analyzed changes in the revenues of local budgets, "Tax revenue" was singled out separately as an item of revenue with the main specific weight. The studied period was set both before the beginning of the reforms and after their implementation in order to compare the changes in the socio-economic indicators of the regions. In addition to revenues, it was important to examine the level of subsidies and changes in local spending priorities. On the basis of statistical information, the main positive and negative consequences of the development of reforms are determined, as well as the aspects of inhibition of the process of formation of sustainable development of regions are determined. Determination of possible ways to improve the administrative management model. To date, constant research and improvement of the management system, financial and economic, social models because there is a high risk of not fulfilling the second stage of sustainable development. That is why the topic is relevant and requires further scientific research.